The changes introduced by the Belgian look-through taxation regulations or Cayman Tax 2.0. Issue 2 (24th December 2018) - Goyvaerts, Gerd D
Abstract: In this article a comment is given on the modifications to the Belgian 'Cayman Tax', applicable since 1 January 2018, and partially applicable since 17 September 2017. Notably, tax regulations on distributions by trusts have been subject to considerable changes, which are highlighted in this contribution. 1